2014
DOI: 10.1097/brs.0000000000000140
|View full text |Cite
|
Sign up to set email alerts
|

Prevertebral Vascular and Esophageal Consideration During Percutaneous Cervical Disc Procedures

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Differences in oesophageal deviation were also observed, with less deviation to the right side (0.63 ± 0.35 cm) than the left (1.18 ± 0.52 cm). An oesophageal diverticulum was also observed in 1 case on the left side 12 .…”
Section: Discussionmentioning
confidence: 88%
“…Differences in oesophageal deviation were also observed, with less deviation to the right side (0.63 ± 0.35 cm) than the left (1.18 ± 0.52 cm). An oesophageal diverticulum was also observed in 1 case on the left side 12 .…”
Section: Discussionmentioning
confidence: 88%
“…Additionally, a large retrospective radiographic study of percutaneous intervention from Jeon et al found that the left C5–6 levels had a significantly higher incidence of vascular structures in the prevertebral areas, thus potentially contributing to our patient’s postoperative complication because her primary intervention was on the left. 5 …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a large retrospective radiographic study of percutaneous intervention from Jeon et al found that the left C5-6 levels had a significantly higher incidence of vascular structures in the prevertebral areas, thus potentially contributing to our patient's postoperative complication because her primary intervention was on the left. 5 Management of such complications have not, to date, been reported in the literature, likely because of the novelty of this technique and overall complication infrequency. We do, however, argue for managing these patients in a fashion similar to those for comparable injuries after classic anterior approaches.…”
Section: Lessonsmentioning
confidence: 99%
See 2 more Smart Citations